2017
DOI: 10.1021/jacs.7b04393
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Electrosynthesis with High Selectivity under Ambient Conditions via a Li+ Incorporation Strategy

Abstract: We report the discovery of a dramatically enhanced N electroreduction reaction (NRR) selectivity under ambient conditions via the Li incorporation into poly(N-ethyl-benzene-1,2,4,5-tetracarboxylic diimide) (PEBCD) as a catalyst. The detailed electrochemical evaluation and density functional theory calculations showed that Li association with the O atoms in the PEBCD matrix can retard the HER process and can facilitate the adsorption of N to afford a high potential scope for the NRR process to proceed in the "[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
383
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 563 publications
(392 citation statements)
references
References 33 publications
9
383
0
Order By: Relevance
“…[1][2][3][4] From an energy-saving perspective,g reen N 2 to NH 3 fixation methods are strongly desired because the main industrial process for producing NH 3 -the Haber-Bosch process-requires extremely harsh reaction conditions (400-600 8 8C, 20-40 MPa) and causes pollution and greenhouse gas emissions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts.…”
mentioning
confidence: 99%
“…[1][2][3][4] From an energy-saving perspective,g reen N 2 to NH 3 fixation methods are strongly desired because the main industrial process for producing NH 3 -the Haber-Bosch process-requires extremely harsh reaction conditions (400-600 8 8C, 20-40 MPa) and causes pollution and greenhouse gas emissions. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] However,t he efficiency of the NRR suffers from ap arallel hydrogen evolution reaction (HER) in aqueous solutions on traditional NRR electrocatalysts.…”
mentioning
confidence: 99%
“…under ambient conditions.D ensity functional theory calculations reveal that the active orbital and electrons of zigzag and diff-zigzag type edges of FL-BP NSs enable selective electrocatalysis of N 2 to NH 3 via an alternating hydrogenation pathway.T his work proves the feasibility of using an onmetallic simple substance as an itrogen-fixing catalyst and thus opening an ew avenue towardst he development of more efficient metal-free catalysts. [4][5][6] However,o wing to the strong dipole moment of the N N triple bond and the vigorous competing hydrogen evolution reaction (HER), [7][8][9][10][11] the development of highly effective catalysts with sufficient activity and selectivity is essential. [1] At present, the energyintensive Haber-Bosch process is the main artificial synthesis route for ammonia, and this process uses more than 1% of global annual energy consumption and produces carbon dioxide emissions.…”
mentioning
confidence: 99%
“…Their general formula is recorded as M n+1 X n T x , where "M" stands for the transition metal element, "X" is C or N or CN, while T x represents the terminal groups of -OH or -F, etc., and n could be 1, 2, or 3. [12,45] Meanwhile, since the marginal titanium atoms on the Ti 3 C 2 T x MXenes surface are thermodynamically metastable, which could act as nucleating sites to enable the generation of relatively stable TiO 2 , thereby a heterojunction structure of TiO 2 nanoparticles (NPs) distributed at the 2D Ti 3 C 2 T x nanosheets (TiO 2 /Ti 3 C 2 T x ) could be facilely formed. [44] Recent studies have revealed the great applicability of the Ti 3 C 2 T x MXene as electrocatalyst in NRR, but there still remains large space for improving both the NH 3 yield and the Faradaic efficiency (FE).…”
mentioning
confidence: 99%